Identity construction and code switching in english newspaper advertisements / Deborah Ashabai S. Fredericks John - S. Fredericks John, Deborah Ashabai (2012)
Identity construction and code switching in print advertising has become an area of growing interest. However, studies on this topic in the Malaysian context are limited. Globally there are significantly more studies conducted, but most scholars investigate the occurrence of English lexical items in local language advertising. Thus, an examination of code switching in advertisements in the Malaysian context would be significant. This study aims to examine the construction of identity through the use of code switching in English newspaper advertisements in Malaysia. Specifically, this study examines how code switching is used to construct identity, determine the types of identities constructed and explore the reasons for the construction of such identities in English newspaper advertisements in Malaysia. To achieve the aims of this study, 121 food, finance, motoring, energy and telecommunication English advertisements with Malay, Tamil and Chinese code switching occurrences were selected. The advertisements were taken from the three local English newspapers with the highest circulation, namely, The Star, The New Straits Times, and The Sun over a period of six months from 1st August, 2011 to 31st January, 2012. The data was analyzed using Bhatia’s (1992) four structural components of advertisements, Piller’s (2001) identity theory of similarity and difference and Woodward’s (1997) theory of difference and representation. The findings reveal that advertisers construct identity through code switching during festivals which are found in the headline and body copy components of their advertisements. Through code switching, different types of identities are constructed, namely, Islamic identity, ethnic identities, National (Malaysian) identity and interest group identities. The main reason for advertisers to construct these identities through code switching is to persuade multilingual consumers. Therefore code switching is used as a marketing strategy. The advertisers aim to persuade consumers through the construction of these identities to accommodate the bilingual consumers, attract consumers through affective means, and build credibility and solidarity with the consumers. The findings are consistent with previous studies on language choice and advertising.